2019
DOI: 10.1186/s13018-019-1296-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood management in fast-track orthopedic surgery: an evidence-based narrative review

Abstract: Background and purpose: Innovations able to maintain patient safety while reducing the amount of transfusion add value to orthopedic procedures. Opportunities for improvement arise especially in elective procedures, as long as room for planning is available. Although many strategies have been proposed, there is no consensus about the most successful combination. The purpose of this investigation is to identify information to support blood management strategies in fast-track total joint arthroplasty (TJA) pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 191 publications
1
31
0
Order By: Relevance
“…According to a randomized controlled trial, accelerated TKA resulted in significantly lower knee pain scores and improved functional outcomes 7 days after surgery [32]. An evidence-based review on blood management in Total Joint Arthroplasty (TJA) underlined how accelerated pathways provide useful room for perioperative planning and prediction, generating additional value in comparison to a conventional protocol [9]. A prospective cohort study reported improved function, quality of life, reduced pain, and better Patient-Related Outcome Measurements (PROMs) after accelerated total hip arthroplasty (THA) [40].…”
Section: Efficacymentioning
confidence: 99%
See 3 more Smart Citations
“…According to a randomized controlled trial, accelerated TKA resulted in significantly lower knee pain scores and improved functional outcomes 7 days after surgery [32]. An evidence-based review on blood management in Total Joint Arthroplasty (TJA) underlined how accelerated pathways provide useful room for perioperative planning and prediction, generating additional value in comparison to a conventional protocol [9]. A prospective cohort study reported improved function, quality of life, reduced pain, and better Patient-Related Outcome Measurements (PROMs) after accelerated total hip arthroplasty (THA) [40].…”
Section: Efficacymentioning
confidence: 99%
“…chronic) or conditions of risk. Despite accelerated pathways show improved accessibility to protected categories of patients [9,51,52], their safety remains controversial [53][54][55][56][57][58].…”
Section: Equitymentioning
confidence: 99%
See 2 more Smart Citations
“…Orthopedic surgeries often require blood transfusion. 9 There should be proper assessment of hemoglobin before surgery as it is seen that that patients with anemia have more risk of surgical complications and death especially during orthopedic surgeries because of the large quantities of blood loss due to bone trauma and the difficulties of achieving hemostasis in this tissue. If hemoglobin level is less than 6% the risk may increase up to 30%.…”
Section: Blood Transfusionmentioning
confidence: 99%